PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN PESERTA DIDIK MEMECAHKAN MASALAH PADA MATERI ZAT ADITIF - Devina Tri Yuliana, Enny Susiyawati (JIP: Jurnal Ilmu Pendidikan, 2024)
Problem-solving ability is one of the important abilities that students must have because, in everyday life, everyone is always faced with various problems that must be solved and requires creativity to be able to find solutions to the problems they face. The aim of this research is to obtain a description of the effectiveness of applying the Problem-Based Learning (PBL) learning model to additive substance material on students' ability to solve problems in terms of the results of increasing problem-solving abilities, the implementation of the PBL learning model, and responses. learners. This research method is quantitative with a quasi-experimental design. Data was collected using observation and test techniques. Observation techniques are used to ensure the learning process is carried out; test techniques are used to see improvements in problem-solving abilities; and for student responses, a questionnaire sheet is used. The results of the research showed that the effect size was 0.923, and the implementation of the learning process received a mode score of 4, which means it was implemented very well and received a positive response from students. Thus, it can be concluded that the problem-based learning model can be used to improve problem-solving abilities with indicators of understanding the problem, planning a solution, resolving the problem according to plan, and checking the results obtained again.